A Mist Connection An Environmental History of the Laki Eruption of 1783 and Its Legacy - Kleemann, Katrin (Historical Catastrophe Studies / Historische Katastrophenforschung, 2023)
In 1783, an eruption occurred in Iceland. Soon after, a dry fog descended upon mainland Europe. These two events long went unconnected. "A Mist Connection" documents the Laki eruption and its consequences for Iceland and the wider world. The book combines methods of historical disaster research, climate history, global history, history of science, and geology in an interdisciplinary approach.